Turning the tide? Why ‘development instead of migration' policies are bound to fail - de Haas, H (International Migration Institute, 2006)
Restrictive immigration policies and the militarisation of external border controls by the US and the EU have failed to significantly curb immigration from Latin America and Africa. Rather, they have led to greater reliance on increasingly risky and costly undocumented migration and have paradoxically encouraged permanent settlement. A commonly presented 'smart solution’ to curb immigration is to address the perceived root causes of migration through increasing aid to or liberalising trade with countries. Recently, policies to stimulate remittances and promoting temporary and circular migration are often promoted as enhancing home country development, so that migration paradoxically becomes a medicine against migration. However, besides the limited scope and credibility of such policies, empirical and theoretical evidence strongly suggests that economic and human development increases people’s capabilities and aspirations and therefore tends to coincide with an increase rather than a decrease in migration, at least in the short to medium term. Under unfavourable conditions, trade, aid and remittances become complementary to rather than substitutes for migration in the long term also. At the same time, demand for both skilled and unskilled migrants is likely to persist. Trade, aid, return migration and remittances are not short-cut 'solutions’ to migration and, therefore, sustained immigration seems to be likely.